New Perspective on Writing History during the Glory of the Islamic Empire in the Archipelago - Ilyas, Yusran; Padiatra, Aditia Muara (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2024)
This journal discusses a new perspective on history in the XV-XVII centuries in the archipelago. This new perspective tries to balance the orientalist perspective and perfect the local perspective in depicting history during the Islamic kingdoms in the archipelago. This new perspective at least reduces the historical narrative that explains the superiority of "outsiders" in determining the fate of the archipelago. Then, this perspective will enrich the theme of Indonesian history which generally only pays attention to political and social issues in this era. At least, the narrative during this period shows the sophistication of thinking of local rulers who were able to create the archipelago into one of the centers of gravity for world trade. This is at least shown and discussed in depth. To obtain fragments of events that support the researcher's statement, a historical method is needed to select fragments of events through several sources, assemble them, and analyze them in depth.